KEMAMPUAN MEMAHAMI BAHASA SISWA KELAS SATU DI SDN 005 BUKIT RANAH KECAMATAN KAMPAR - Hidayatun Nur (Jurnal Educhild : Pendidikan dan Sosial, 2018)
Preparing children before entering elementary school needs to be done. One way that can bedone is to provide education before elementary school. This education can be provided in PAUD.Preparation of children entering elementary school, one of which is children can understandlanguage. Children who have the ability to understand language will be able to interact with theirenvironment. From the results of research conducted at 005 Public Elementary School BukitRanah, Kampar District, Kampar District, it is known that two indicators are still in the category ofdeveloping (MB), namely Understanding the rules in a game and Happy and appreciating readingand two categories included in the category of developing according to expectations (BSH )Understand several commands simultaneously and repeat more complex sentences. Mempersiapkan anak sebelum memasuki sekolah dasar perlu untuk dilakukan. Salah satu carayang dapat dilakukan adalah dengan memberikan pendidikan sebelum sekolah dasar. Pendidikantersebut dapat diberikan di PAUD. Persiapan anak memasuki sekolah dasar salah satunyaadalah anak dapat memahami bahasa. Anak yang memiliki kemampuan memahami bahasaakan dapat beriteraksi dengan lingkungannya. Dari hasil penelitian yang dilakukan di SekolahDasar Negeri 005 Bukit Ranah Kecamatan Kampar Kabupaten Kampar diketahui dua indikatormasih masuk dalam kategori mulai berkembang (MB) yaitu Memahami aturan dalam suatupermainan dan Senang dan menghargai bacaan serta dua kategori termasuk dalam kategoriberkembang sesuai harapan (BSH) Mengerti beberapa perintah secara bersamaan danMengulang kalimat yang lebih kompleks.